1986
DOI: 10.1002/j.1551-8833.1986.tb05804.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Coagulation on Removal of Organics by Granular Activated Carbon

Abstract: Coagulation of Mississippi River water improved the removal of total organic carbon (TOC) and trihalomethane precursors by granular activated carbon. This increased removal is thought to be due to the reductions in TOC and in poorly adsorbed higher‐molecular‐weight organics that are achieved by coagulation. A cost analysis indicated that very high coagulant dosages would be needed during pretreatment to minimize the overall costs of chemical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Higher alum dosages have been shown to improve GAC performance for TOC, ultraviolet absorbance at 254 nm (UV 254 ), and TTHM precursor removal for Mississippi River water (MRW). 12 Improved GAC performance after more extensive coagulation has been attributed to three factors: (1) lower influent TOC concentration, (2) lower influent pH, and (3) an improvement in the adsorbable character of NOM. Several studies have demonstrated that adsorption capacity increases with decreasing initial TOC concentration utilizing batch isotherm tests.…”
Section: Figurementioning
confidence: 99%
“…Higher alum dosages have been shown to improve GAC performance for TOC, ultraviolet absorbance at 254 nm (UV 254 ), and TTHM precursor removal for Mississippi River water (MRW). 12 Improved GAC performance after more extensive coagulation has been attributed to three factors: (1) lower influent TOC concentration, (2) lower influent pH, and (3) an improvement in the adsorbable character of NOM. Several studies have demonstrated that adsorption capacity increases with decreasing initial TOC concentration utilizing batch isotherm tests.…”
Section: Figurementioning
confidence: 99%
“…The effectiveness of GAC treatment depends on NOM characteristics, including concentration and molecular size. These characteristics can be a function of pH or the effect of pretreatment processes such as coagulation and ozonation (Hooper et al, 1996; Semmens et al, 1986a, 1986b). In drinking water treatment, NOM is often quantified by a surrogate parameter such as TOC or dissolved organic carbon (DOC).…”
Section: Introductionmentioning
confidence: 99%